Sputum pentraxin 3 as a candidate to assess airway inflammation and remodeling in childhood asthma. Issue 51 (December 2016) - Kim, Min Jung; Lee, Hee Seon; Sol, In Suk; Kim, Mi Na; Hong, Jung Yeon; Lee, Kyung Eun; Kim, Yoon Hee; Kim, Kyung Won; Sohn, Myung Hyun; Kim, Kyu-Earn
Abstract : Abstract: Pentraxin 3 (PTX3) is a soluble pattern recognition receptor and an acute-phase protein. It has gained attention as a new biomarker reflecting tissue inflammation and damage in a variety of diseases. Aim of this study is to investigate the role of PTX3 in childhood asthma. In total, 260 children (140 patients with asthma and 120 controls) were enrolled. PTX3 levels were measured in sputum supernatants using enzyme-linked immunosorbent assay test. We performed spirometry and methacholine challenge tests and measured the total eosinophil count and the serum levels of total IgE and eosinophil cationic protein (ECP) in all subjects. Sputum PTX3 concentration was significantly higher in children with asthma than in control subjects ( P < 0.001). Furthermore, sputum PTX3 levels correlated with atopic status and disease severity among patients with asthma. A positive significant correlation was found between sputum PTX3 and the bronchodilator response ( r = 0.25, P = 0.013). Sputum PTX3 levels were negatively correlated with forced expiratory volume in 1 second (FEV1 ) ( r = -0.30, P = 0.001), FEV1 /forced vital capacity (FVC) ( r = -0.27, P = 0.002), and FEF25–75 ( r = -0.392, P < 0.001), which are indicators of airway obstruction and inflammation. In addition, the PTX3 concentration in sputum showed negative correlations with post-bronchodilator (BD) FEV1 ( r = -0.25, P < 0.001) and post-BD FEV1 /FVC ( r = -0.25, P < 0.001), which are parameters of persistent airflow limitation reflecting airway remodeling. Sputum PTX3 levels increased in children with asthma, suggesting that PTX3 in sputum could be a candidate molecule to evaluate airway inflammation and remodeling in childhood asthma.